2011
DOI: 10.1007/s10825-011-0348-9
|View full text |Cite
|
Sign up to set email alerts
|

Compact modeling and simulation of nanoscale fully depleted DG-SOI MOSFETS

Abstract: A two dimensional analytical model for nanoscale fully depleted double gate SOI MOSFET is presented. Green's function solution technique is adopted to solve the two dimensional Poisson's equation using Dirichlet's and Neumann's boundary conditions at silicon-silicon di-oxide interface. Based on the derived 2D potential distribution, surface potential distributions in the Si film are analytically obtained. The calculated minimum surface potential is used to develop an analytic threshold voltage model. Simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Figure 7 shows front surface potential distribution along the surface channel for L = 65 nm under the specific bias conditions, that is, V bs = 0V, V ds = 0.6V and V gs = 0.3V. Solid curve represents the calculated results using our developed model with the specified source-drain cylindrical junction, and the dashed curve represents results of our recently developed model [14] with rectangular-shaped junction. Moreover, it is obviously shown that the barrier lowering effect for a rectangular-shaped junction is larger than that for a cylindrical junction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 7 shows front surface potential distribution along the surface channel for L = 65 nm under the specific bias conditions, that is, V bs = 0V, V ds = 0.6V and V gs = 0.3V. Solid curve represents the calculated results using our developed model with the specified source-drain cylindrical junction, and the dashed curve represents results of our recently developed model [14] with rectangular-shaped junction. Moreover, it is obviously shown that the barrier lowering effect for a rectangular-shaped junction is larger than that for a cylindrical junction.…”
Section: Resultsmentioning
confidence: 99%
“…where t of (t ob ) is front (back)-gate oxide thickness. Using Greens theorem [14], 2D potential distribution in region 2 is…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation